Federal Republic of Yugoslavia : Membership and Use of Fund Resources-Request for Emergency Post-Conflict Assistance. (IMF Staff Country Reports; Country Report ;, 2001)
The Federal Republic of Yugoslavia is faced with the task of stabilizing and reviving a devastated economy after years of military conflicts, sanctions, and economic mismanagement. A weakened institutional capacity and the still evolving political situation is a cause for concern. A short-term macroeconomic strategy is required to bring down inflation. The fiscal position should be improved, and the continued incurrence of expenditure arrears should be avoided. The government should adopt a comprehensive economic program of stabilization and reform that can be supported by the IMF.